The Legality of Russia’s Special Military Operation Against Ukraine from International Law Perspective - Dananjaya, I Komang; Dhananjaya, Nyoman Satyayudha (Kertha Patrika, 2022)
Russia has launched a Special Military Operation against Ukraine, which resulted in a crisis therein. According to Vladimir Putin, current Russia’s President, the action aimed to exercise the state’s inherent right of individual and collective self-defense for the Donetsk People’s Republic (‘DPR’) and Luhansk People's Republic (‘LPR’). This article was aimed to analyze the legality of Russia’s use of force. This article applied normative legal research and using statutory, case, conceptual, and fact approaches in analyzing the case. The study indicated that Russia’s Special Military Operation constitutes illegal use of force. Based on the criteria set in international law, Russia’s justification for individual self-defense is invalid since no armed attack exists, unnecessary and unproportionate. As well as its collective selfdefense plea, which does not apply in these circumstances as DPR and LPR statehood is not clear, let alone its United Nations membership status. Suppose that it does apply, the use of force is still unlawful since other non-forcible means are available to achieve the end sought.